Book Review: Merawat Wajah Keindonesiaan Allah: Pergulatan Iman Publik (Seorang) Protestan Indonesia - Tambunan, Elia (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
Indonesia is a remarkable unitary republic, enriched by its diverse people, religions, and races. It's essential to recognize the value of this diversity that makes up the 1001 faces of Indonesia. However, there are still instances of pain caused by the elimination of one group by another. In an effort to bridge this gap, Julianus Mojau has written a collection of popular writings that reflect on the struggles of the Indonesian Protestant faith. Through his reflections, he shares his insights and experiences on the idea of Indonesian social struggle from 2005-2018, emphasizing the intersection between Christian faith and politics in Indonesia. Julianus is an excellent example of academics and practitioners who take a courageous path towards caring for the face of Indonesia. By bridging the differences in religion, ethnicity, aspirations, and political ideology, they strive to strengthen Indonesia's national and state identity.